Examining the mental health symptoms of neurodivergent individuals across demographic and identity factors: a quantitative analysis - Kroll, Elizabeth; Lederman, Megan; Kohlmeier, Jonathan; Ballard, Jaime; Zant, Izabella; Fenkel, Caroline (Frontiers in Psychology, 2025)
BackgroundNew research indicates that neurodivergent individuals experience unique intersections of identities at a much higher rate than historical research suggested. Factors such as race, gender, and sexuality interact with neurodivergent identities to influence their lived experiences and healthcare needs. While intersectionality has gained traction in research, the intersection of neurodivergence with other marginalized identities remains underexplored.ObjectiveThis study seeks to fill this gap by examining how various social identities interact with neurodivergence to mediate mental health symptoms. Understanding these interactions is crucial for developing inclusive mental healthcare practices that affirm neurodivergent identities and address disparities in mental health outcomes among marginalized populations.MethodsData was collected between May 2023 and March 2024 from 14,219 individuals admitted to a virtual intensive outpatient mental health treatment program. Clients self-reported demographic information, including neurodivergent identity, gender, sexual orientation, and race. Two-way MANOVAs were run to assess the interactions between different identities and the impact that those interactions had on anxiety and depression scores at both intake and discharge. When MANOVAs indicated significant interactions, follow-up two-way ANOVAs were conducted for each dependent variable.ResultsSexual and gender minority respondents were more likely to identify as neurodivergent compared to their straight and gender binary counterparts. Significant interactions were found between neurodivergence and gender on depression, as well as neurodivergence and sexual orientation on both depression scores and anxiety scores. However, no significant interactions were found between neurodivergence and racial identity with respect to depression or anxiety scores.DiscussionThe complex interplay between neurodivergent identity and additional marginalized identities has a significant impact on how mental health symptoms are experienced, and therefore should have a significant impact on how treatment is tailored to the individual. By providing identity-affirming care, individuals are given the space to process their mental health symptoms in an empowering and less stressful environment.